2021
DOI: 10.1002/tpg2.20123
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in the Sorghum genus based on sequencing of the chloroplast and nuclear genes

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is an important food crop with a diverse gene pool residing in its wild relatives. A total of 15 sorghum accessions from the unexploited wild gene pool of the Sorghum genus, representing the five subgenera, were sequenced, and the complete chloroplast genomes and 99 common single-copy concatenated nuclear genes were assembled. Annotation of the chloroplast genomes identified a total of 81 protein-coding genes, 38 tRNA, and four rRNA genes. The gene content and gene order a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…Access to preliminary genome sequence data for six CWR ( S. laxiflorum , S. macrospermum , S. brachypodum , S. leiocladum , S. matarankense and S. purpureosericeum [ 35 ]) enabled the analysis of the variation present in selected genes involved in cyanogenesis and related pathways. Briefly, the trimmed reads were mapped to the genomic sequences of the 18 selected S. bicolor genes ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to preliminary genome sequence data for six CWR ( S. laxiflorum , S. macrospermum , S. brachypodum , S. leiocladum , S. matarankense and S. purpureosericeum [ 35 ]) enabled the analysis of the variation present in selected genes involved in cyanogenesis and related pathways. Briefly, the trimmed reads were mapped to the genomic sequences of the 18 selected S. bicolor genes ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The available sequences of a series of selected genes in the genomes of 6 wild sorghum species [ 35 ] were used to analyze the variation in 18 genes selected based on known and putative roles in cyanogenesis (dhurrin biosynthesis, bioactivation, recycling) as well as in the synthesis of tyrosine (the amino acid substrate for the first step in dhurrin biosynthesis) and ethylene ( Supplementary Table S2 ). The S. bicolor genomic sequences for these genes were downloaded to CLC from Phytozome ( , accessed on 10 January 2022) and used to map the reads generated from the partial sequencing of the six wild Sorghum species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, wild sorghum species such as S. macrospermum with a very low dhurrin content in their leaves can be “redomesticated” by introducing genes related to higher yield and biomass from the already domesticated sorghum species e.g., as shown in wild tomato (Lemmon et al 2018 ; Zsögön et al 2018 ). The close phylogenetic relationship of domesticated S. bicolor and the wild species S. macrospermum (Ananda et al 2021 ) provides a great advantage to the introgression of beneficial traits of sorghum species.…”
Section: Discussionmentioning
confidence: 99%
“…A major constraint in utilising the genetic resources in wild crop relatives is hindrance in gene transfer between domesticated crops and their wild relatives (Bevan et al 2017 ). However, the Australian endemic wild sorghum species, S. macrospermum is closely related to domesticated S. bicolor (Ananda et al 2021 ), with successful introgression of the two species reported by Kuhlman et al ( 2010 ). The regulation of the synthesis of dhurrin in wild sorghum species in comparison to domesticated S. bicolor has not been studied.…”
Section: Introductionmentioning
confidence: 99%